Mastering Java for Data Science - Grigorev, Alexey; Grigorev, Alexey (Packt Publishing, 2017)
Use Java to create a diverse range of Data Science applications and bring Data Science into productionAbout This BookAn overview of modern Data Science and Machine Learning libraries available in JavaCoverage of a broad set of topics, going from the basics of Machine Learning to Deep Learning and Big Data frameworks.Easy-to-follow illustrations and the running example of building a search engine.Who This Book Is ForThis book is intended for software engineers who are comfortable with developing Java applications and are familiar with the basic concepts of data science. Additionally, it will also be useful for data scientists who do not yet know Java but want or need to learn it.If you are willing to build efficient data science applications and bring them in the enterprise environment without changing the existing stack, this book is for you!What You Will LearnGet a solid understanding of the data processing toolbox available in JavaExplore the data science ecosystem available in JavaFind out how to approach different machine learning problems with JavaProcess unstructured information such as natural language text or imagesCreate your own search engineGet state-of-the-art performance with XGBoostLearn how to build deep neural networks with DeepLearning4jBuild applications that scale and process large amounts of dataDeploy data science models to production and evaluate their performanceIn DetailJava is the most popular programming language, according to the TIOBE index, and it is a typical choice for running production systems in many companies, both in the startup world and among large enterprises.Not surprisingly, it is also a common choice for creating data science applications: it is fast and has a great set of data processing tools, both built-in and external. What is more, choosing Java for data science allows you to easily integrate solutions with existing software, and bring data science into production with less effort.This book will teach you how to create data science applications with Java. First, we will revise the most important things when starting a data science application, and then brush up the basics of Java and machine learning before diving into more advanced topics. We start by going over the existing libraries for data processing and libraries with machine learning algorithms. After that, we cover topics such as classification and regression, dimensionality reduction and clustering, information retrieval and natural language processing, and deep learning and big data.Finally, we finish the book by talking about the ways to deploy the model and evaluate it in production settings.Style and approachThis is a practical guide where all the important concepts such as classification, regression, and dimensionality reduction are explained with the help of examples.